Perfil de liderança pela percepção do lider e de seus colaboradores: um estudo de caso em uma empresa do agronegócio no município de Dom Pedrito/RS - (:unkn) unknown (Universidade Federal do Pampa, 2014)
Leadership has great influence on people, it is essential in all types of organization, whether in business or in each of its sectors. Leadership is very important in all functions of management, so the administrator knows human nature and leads to people, practicing leadership, therefore, this study aimed to identify the leadership profile manager falls and employees have the same perception about the leadership style of it. The method was applied to a case study. This research contributed to leadership and employees understand the importance of leadership for the progress of a company. It was found that the company studied the predominant leadership of the manager is Democratic, the profile of who delegates appropriately, the leader leads and guides the group encouraging people to participate. Leadership and employees develop spontaneous reports, there is a large group cohesion in a climate of satisfaction. This work contributed to the leadership and employees to gain knowledge about the styles of leadership and its importance in organizations.
Keywords: Gestão de pessoas; Líder; Liderança; People management; Leader; Leadership; CNPQ::CIENCIAS EXATAS E DA TERRA